Home/Work: The Rhetoricity of Commemorative Labor at the Belmont-Paul House. Issue 1 (1st January 2023) - Keohane, Jennifer
Abstract : Tucked away on Capitol Hill, the Belmont-Paul Women's Equality National Monument honors suffrage pioneers Alva Belmont and Alice Paul. I argue that the Belmont-Paul House tells a metanarrative on the curation of women's history, which scholars can read through investigating the commemorative labor visible in this memory place. Belmont-Paul reflexively calls attention to its own creation, making visible the labor of preserving the house, gathering artifacts, and weaving a narrative of the story of the struggle for suffrage. In seeking clues to the gendered work that goes into public memorializing, critics can access valuable metanarratives about history and the rhetorical choices that are opened or foreclosed in a place.